2004
DOI: 10.2196/jmir.6.4.e43
|View full text |Cite
|
Sign up to set email alerts
|

Parents of Urban Adolescents in Harlem, New York, and the Internet: A Cross-sectional Survey on Preferred Resources for Health Information

Abstract: Background Vulnerable populations suffer disproportionately from a variety of health conditions. Access to health information is an important component of health promotion. Reports suggest that while health providers and print media are traditional sources of information, the Internet may be becoming an increasingly important resource for consumers. Particularly, for parents of urban adolescents of color, the Internet could prove to be a valuable asset in helping them understand adolescent health and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Linebarger and Chernin (2003) found that parents reported feeling more comfortable using a computer if they owned one and more strongly agreed that people got left behind if they did not know about computers. However, in another study, African American and Latino parents who largely had access to the Internet reported they did not search much for health information online (Cohall et al, 2004). This gap between access and use may be due to a lack of comfort with technology as many of these parents expressed a desire to learn more about the Internet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linebarger and Chernin (2003) found that parents reported feeling more comfortable using a computer if they owned one and more strongly agreed that people got left behind if they did not know about computers. However, in another study, African American and Latino parents who largely had access to the Internet reported they did not search much for health information online (Cohall et al, 2004). This gap between access and use may be due to a lack of comfort with technology as many of these parents expressed a desire to learn more about the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found disparities in technology access by race, others have found differences disappear at higher income levels (Plantin & Daneback, 2009). In one study, urban families of color tended to have high levels of access to the Internet (77%) even though 46% of the families were considered low income; however, only 14% of the families searched the Internet for health information (Cohall, Cohall, Dye, Dini, & Vaughan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohall et al documented computer ownership in more than 84% of urban adolescents in Harlem. 8 Similarly, studies have described expanding computer access among other minority and underserved populations. 9 Among patients in an urban, tertiary-care center, we found that 78% of upper extremity patients reported owning a computer.…”
Section: Discussionmentioning
confidence: 99%
“…In real life, there is also a great variation in patients regarding how they want to receive health information: there are patients who have already started to require e-mail and/or wireless application protocol communication to be included in hospital-patient communication [6,31], while there are patients who do not benefit or have enough motivation to use computers to find health information [32]. One solution to this wide variation is a systematic evaluation of patients' educational needs.…”
Section: Discussionmentioning
confidence: 99%